Application of Herbal Plants in Organic Poultry Nutrition and Production - Shahrajabian, Mohamad H.; Cheng, Qi; Sun, Wenli (Current Nutrition & Food Science, 2022)
Background: Medicinal plants and natural feed additives are the most important alternatives in animal production, especially in broiler production. Objective: In this mini-review article, some important medicinal herbs and plants with positive effects on organic broiler production have been highlighted. Methods: A literature search was conducted using Science Direct, Google, Google Scholar, Springer, Medline, and PubMed. Results: Medicinal plants such as ginger, ginkgo, thyme, ponderosa pine, soybean, forsythia, peppermint, Chinese star anise, astragalus, mistletoe, schisandra, cumin, capsicum, garlic, hooker chives, artichoke, Borreria latifolia, zataria, pomegranate, turmeric, lingzhi, Lippia javanica, neem, oriental chaff flower, mulberry leaf, goji berry, Aloe vera, pumpkin, grape, common nettle, marigold, coriandrum, Citrus sinensis, Alisma canaliculatum, Persian hogweed, Eucommiaulmoides, bamboo leaf extract, rosemary, Morina citrifolia, chestnut, green tea, wild mint, clove, sumac, satureja, ashwagandha, Lonicera japonica, Acacia, liquorice, Artemisia annua, milk thistle, cinnamon, black cumin, etc., have positive effects on organic broiler production. Conclusion: Herbal medicines lead to increased body weight due to a higher feed intake and a higher feed conversion ratio. They improve the antioxidant activity of broiler chickens based on their phenolic compound contents. The combination of medicinal herbal additives also has a positive impact on broiler production. Reducing hormones, growth promoters, and antibiotics, as well as addressing appropriate organic feed management and higher production, should be organized in organic broiler production with the use of herbal plants.
Keywords: Organic broiler production